Samantha Beck: capstone - Beck, Samantha, artist (Colorado State University. Libraries, 2016)
The artist's statement: As an artist I grow older and wiser in my practices. I learn something new with every click I make with my computer while creating a graphically appealing design. When I was younger and someone asked me what I wanted to be when I grew up, I never thought I would say, "I want to be a graphic designer". Now, it is something that is truly thrilling to me. My work that I have had the most fulfillments in creating is when I am able to take an existing story and interpret it as I see fit. The freedom to be able to take an idea and morph it into something new and exciting for the viewer is something that makes me proud of myself and proud of my work. To see an opportunity for a new creation is to see nothing but treasures yet to be found.
Colorado State University Art and Art History Department capstone project.
Capstone contains the artist's statement, a list of works, and images of works.
Keywords: graphic design